2002
DOI: 10.1021/jf020615a
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Prooxidant Effects of Phenolics on Pancreatic β-Cells in Vitro

Abstract: A number of natural phenolic compounds display antioxidant and cell protective effects in cell culture models, yet in some studies show prooxidant and cytotoxic effects. Pancreatic beta-cells have been reported to exhibit particular sensitivity to oxidative stress, a factor that may contribute to the impaired beta-cell function characteristic of diabetes. The aim of this study was to examine the potential of natural phenolics to protect cultured pancreatic beta-cells (betaTC1 and HIT) from H(2)O(2) oxidative s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(109 citation statements)
references
References 50 publications
3
106
0
Order By: Relevance
“…For example, hydrogen peroxide is generated in simian virus 40-transformed hamster pancreatic b-cells (HIT) in the presence of 50 mM quercetin or chrysin, 21) and ROS are generated in human thymoma-derived cells (HPB-ALL) in the presence of 50 mM quercetin 39) and in Jurkat cells in the presence of 110-880 mM baicalin (baicalein 7-b-D-glucopyranosiduronate). 40) As shown above, our observations show that ROS are generated in normal human cells in the presence of flavonoids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, hydrogen peroxide is generated in simian virus 40-transformed hamster pancreatic b-cells (HIT) in the presence of 50 mM quercetin or chrysin, 21) and ROS are generated in human thymoma-derived cells (HPB-ALL) in the presence of 50 mM quercetin 39) and in Jurkat cells in the presence of 110-880 mM baicalin (baicalein 7-b-D-glucopyranosiduronate). 40) As shown above, our observations show that ROS are generated in normal human cells in the presence of flavonoids.…”
Section: Discussionmentioning
confidence: 99%
“…16) Further, it has been reported that they exert cytotoxicity at higher concentrations and in the presence of oxidation-catalyzing factors such as transition metal ions. The cytotoxicity of flavonoids toward human promyelocytic leukemia cells (HL-60), 17) human acute myelogeneous leukemia cells (KG1, KG1a, THP-1, and U937), 18) rhesus monkey kidney cells (LLC-MK2), rat glial tumor cells (C6), 19) bovine leukemia virus-transformed lamb embryo kidney fibroblasts (FLK), 20) mouse and hamster pancreatic b-cells (b TC1 and HIT), 21) human fibroblasts (HFK-2), human keratinocytes (HaCaT), human breast cancer adenocarcinoma cells (MCF-7), human neuroblastoma cells (SHEP and WAC-2), and bovine capillary endothelial cells 22) has been found. As shown above, however, there are only a few reports on the cytotoxicity of flavonoids toward human normal cells.…”
mentioning
confidence: 99%
“…Chrysin (5,7-dihydroxyflavone) is a natural flavonoid presented in many plant extracts, including blue passion flower (Passiflora caerulea), honey and propolis (10). A number of studies have shown that chrysin has multiple biological activities, such as antiinflammation, antioxidation and anticancer effects (11)(12)(13). Chrysin has been reported to induce apoptosis in a panel of cancer cell lines, including HeLa cervical cancer cells, U937, HL-60 and L1210 leukemia cells (14).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, artifactual bioactivity could be generated (increased glycerol release and lipolysis) by use of this method for testing plant extracts. Lapidot et al [44][45] examined in greater details the possibility of phenolics in apple extracts interacting with components in the cell culture media that resulted in the generation of hydrogen peroxide (H 2 O 2 ). This newly formed product was found to cause the inhibition of the proliferation of tumor cells in vitro.…”
Section: Interpretation Of the Screening Results -Keep Or Drop?mentioning
confidence: 99%